Outcomes of Feeding Training to Mothers Having Child with Cerebral Palsy Admitted at A Tertiary Level Hospital in Bangladesh (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2017)
Background: The majority of children with Cerebral Palsy have feeding difficulties. It has a great impact on growth and development in children with cerebral palsy. Feeding difficulties may leads to chronic respiratory disease, malnutrition and reduce quality of life of both children and caregiver. Feeding difficulties cause stressful meal time for caregivers and fear of food for children. In well resource country many hi-tech equipments for the management of feeding difficulties are available but which is not available in low resource country like Bangladesh. Though some of low tech approaches have started a little but the effectiveness or outcomes of these technologies are not evaluated. This study is aimed to evaluate the effect of feeding training on feeding difficulties in children with cerebral palsy.Methods: This is a quasi experimental study. Twenty children with cerebral palsy aged 2 9 years having feeding difficulties enrolled as study subjects. Initially degree of feeding difficulties were assessed by evaluating body posture and frequency of aspiration during feeding which is scored according to the response of the child. After giving feeding training to the mother feeding difficulties were reevaluated. Mean score of feeding difficulties before and after intervention were compared by paired 't' test. Results were analyzed by SPSS.Results: Among the study subject 14(70%) were male and 6(30%) were female. Most of them were found to have hemiplegic CP 7(35%). The mean score in terms of positioning and frequency of aspiration were significantly changed after intervention (14.15 vs. 15.85 p =